1991
DOI: 10.1103/physreva.43.749
|View full text |Cite
|
Sign up to set email alerts
|

Onset of convection for autocatalytic reaction fronts: Laterally unbounded system

Abstract: The linear stability of exothermic autocatalytic reaction fronts that convert unreacted fluid into a lighter reacted fluid is considered using the viscous thermodynamic equations. For upward front propagation and a thin front, the discontinuous jump in density at the front is reminiscent of the Rayleigh-Taylor problem of an interface between two immiscible fluids, whereas the vertical thermal gradient near the front is reminiscent of the Rayleigh-Benard problem of a fluid layer heated from below. The problem i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 19 publications
3
64
1
Order By: Relevance
“…This relation, an asymptotic form of the reaction-diffusion equations for wave propagations, has been successfully applied to spiral waves in the BZ reaction [10] as well as to convective chemical waves in the iodate-arsenous acid systems [8,14]. In our case (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This relation, an asymptotic form of the reaction-diffusion equations for wave propagations, has been successfully applied to spiral waves in the BZ reaction [10] as well as to convective chemical waves in the iodate-arsenous acid systems [8,14]. In our case (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, since the typical thermal diffusivities (=10 cm /s) are about 100 times greater than typical molecular diffusivities (=10 cm /s), any thermal gradient can be rapidly smoothed out by thermal diffusion, leaving the density gradient practically the same as the purely compositional density gradient at the higher temperature of the reacted Quid. Previous calculations on the iodate-arsenous acid reaction have justified this argument [8]. Therefore, in this paper, we consider only the density gradient induced by changes in chemical composition.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Theoretical work for such narrow geometry provides the critical radius of the tube above which the hydrodynamic instability can develop, and a discussion on whether axi-or nonaxisymmetric modes should be observed at onset. [22][23][24][25][26][27] More recently, experiments in Hele-Shaw cells have shown that several fingers can develop in this geometry where the front is laterally extended. 16 -18,20 Dispersion curves providing the growth rate of the fingers as a function of their wave number have been measured experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…9 In miscible systems, chemical reactions are more prone to provide density differences that can drive buoyantly unstable situations as soon as a heavier fluid lies on top of a lighter one. Experimental evidence [10][11][12][13][14][15][16][17][18][19][20] and theoretical studies [20][21][22][23][24][25][26][27][28][29][30][31][32] on density driven instabilities have shown that the coupling between buoyancy driven flows and chemical reactions can strongly affect the properties of the fingering instability. The coupling with chemical reactions has been addressed mainly concerning the stability of planar fronts with regard to Rayleigh-Taylor fingering.…”
Section: Introductionmentioning
confidence: 99%